2014
DOI: 10.1056/nejmoa1404588
|View full text |Cite
|
Sign up to set email alerts
|

A Modified γ-Retrovirus Vector for X-Linked Severe Combined Immunodeficiency

Abstract: BACKGROUND In previous clinical trials involving children with X-linked severe combined immunodeficiency (SCID-X1), a Moloney murine leukemia virus–based γ-retrovirus vector expressing interleukin-2 receptor γ-chain (γc) complementary DNA successfully restored immunity in most patients but resulted in vector-induced leukemia through enhancer-mediated mutagenesis in 25% of patients. We assessed the efficacy and safety of a self-inactivating retrovirus for the treatment of SCID-X1. METHODS We enrolled nine boy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
281
1
6

Year Published

2015
2015
2017
2017

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 364 publications
(299 citation statements)
references
References 36 publications
9
281
1
6
Order By: Relevance
“…At least 20 genes have been associated with SCID [1]. Currently, curative treatments such as hematopoietic stem cell transplantation (HSCT) [2][3][4] and gene therapy [5][6][7] can improve a patient's outcome if the treatment can be initiated before severe infections occur. Previously, a significant number of children with SCID would die before a diagnosis was made [8] or before a curative treatment could be administered [2,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…At least 20 genes have been associated with SCID [1]. Currently, curative treatments such as hematopoietic stem cell transplantation (HSCT) [2][3][4] and gene therapy [5][6][7] can improve a patient's outcome if the treatment can be initiated before severe infections occur. Previously, a significant number of children with SCID would die before a diagnosis was made [8] or before a curative treatment could be administered [2,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Lentiviral targeted hematopoietic stem cell (HSC) gene therapy has recently achieved steadily accelerating progress for the treatment of hematological diseases, [1][2][3] which includes hemoglobinopathies (sickle cell disease and b-thalassemia). [4][5][6][7] The first clinical trial for b-thalassemia was initiated in 2007.…”
Section: Introductionmentioning
confidence: 99%
“…To shed light on this issue in our trial, we used sequence readcounts to estimate the relative abundances of clones with integrations near a set known leukemiarelated genes generated in another study and near a set of genes homologous to retrovirally tagged cancer gene database (RTCGD) mouse genes identified in hematopoietic cancers caused by retroviral and transposon mutagenesis. 38,39 We compared these estimates with those of all other clones for both gene sets of interest. In both cases, we found that clones with ISs near genes of interest were statistically more abundant, as indicated by the average proportion of sequence reads they accounted for within samples (supplemental Figure 3).…”
Section: Clinically Benign Genotoxicitymentioning
confidence: 99%